Long‐term outcome of inactive and active, low viraemic HBeAg‐negative‐hepatitis B virus infection: Benign course towards HBsAg clearance. (18th April 2017) - Oliveri, Filippo; Surace, Lidia; Cavallone, Daniela; Colombatto, Piero; Ricco, Gabriele; Salvati, Nicola; Coco, Barbara; Romagnoli, Veronica; Gattai, Riccardo; Salvati, Antonio; Moriconi, Francesco; Yuan, Quan; et al.
Abstract: Background & Aims: The difference between the long‐term outcome of low‐viraemic (HBV‐DNA≤20 000‐IU/mL, LV‐AC) and inactive HBsAg carriers (HBV‐DNA≤2000‐IU/mL, IC) remains to be defined. We studied prospectively 153 HBeAg‐negative HBsAg‐carriers with baseline HBV‐DNA≤20 000‐IU/mL and normal transaminases. Methods: IC, LV‐AC or chronic hepatitis B (CHB) (HBV‐DNA persistently ≤2000‐IU/mL, ≤20 000‐IU/mL or >20 000‐IU/mL respectively) were diagnosed after 1‐year, 3‐monthly monitoring. Thereafter IC and LV‐AC were followed‐up for additional 57.2 (8.5‐158.3) months. HBV‐DNA, HBsAg, HBV"core‐related"Antigen (HBcrAg) and total‐anti‐HBc were quantified at baseline. Results: After the 1st year diagnostic follow‐up CHB [higher HBV‐DNA ( P =.005), total‐anti‐HBc ( P =.012), ALT ( P =.007) and liver‐stiffness ( P =.021)] was identified in 20 (13.1%) carriers; baseline HBsAg≤1000IU/HBV‐DNA≤2000IU/mL excluded the presence of CHB (NPV‐100%). Thereafter, during the long‐term follow‐up none of 87 IC reactivated, 19 (21.8%) cleared HBsAg [older‐age ( P =.004), lower HBsAg ( P <.001), higher yearly HBsAg decline ( P <.001)]. Twenty‐five of 46 (54.3%) LV‐AC remained stable, 20 (43.5%) became IC and 1 (2.2%) developed CHB. The best single‐point CHB and IC diagnostic‐accuracies were total‐anti‐HBc (84.2%, NPV‐98.2%) and HBV‐DNA/total‐anti‐HBc/HBcrAg combination (89.5%, 93%‐sensitivity, 84.8%‐specificity) respectively. Conclusions: Viraemia persistently ≤20 000‐IU/mL predicts a benign clinical outcome: it was associated with transition to IC in 43% of LV‐AC and to Occult HBV Infection in 20% of IC within 5‐years. Nevertheless, 13.1% of individuals with low viraemia at presentation develops CHB within 1 year: 1‐year HBV‐DNA monitoring resulted the most accurate diagnostic approach that can be limited to at least a half of cases by the single point HBV‐DNA/HBsAg quantification. The IC‐diagnostic‐accuracy combining HBV‐DNA/total‐anti‐HBc/HBcrAg needs to be confirmed in further studies.